Detonation wave propagation in semi-confined layers of hydrogen–air and hydrogen–oxygen mixtures. (16th March 2017) - Grune, J.; Sempert, K.; Friedrich, A.; Kuznetsov, M.; Jordan, T.
Abstract: This paper presents results of an experimental investigation on detonation wave propagation in semi-confined geometries. Large scale experiments were performed in layers up to 0.6 m filled with uniform and non-uniform hydrogen–air mixtures in a rectangular channel (width 3 m; length 9 m) which is open from below. A semi confined driver section is used to accelerate hydrogen flames from weak ignition to detonation. The detonation propagation was observed in a 7 m long unobstructed part of the channel. Pressure measurements, ionization probes, soot-records and high speed imaging were used to observe the detonation propagation. Critical conditions for detonation propagation in different layer thicknesses are presented for uniform H2 /air-mixtures, as well as experiments with uniform H2 /O2 mixtures in a down scaled transparent channel. Finally detail investigations on the detonation wave propagation in H2 /air-mixtures with concentration gradients are shown. Highlights: Detonation propagation in semi-confined geometries is studied experimentally. Uniform and non-uniform H2 -air mixtures are investigated in large scale. Comparative studies in small scale with H2 /O2 -mixtures are shown. Limits for detonation wave propagation for both mixtures are presented. A method to compare uniform and non-uniform mixtures is shown.